Dispersion of carbon nanotubes into polyethylene by an additive assisted one-step melt mixing approach - Mueller, Michael Thomas; Poetschke, Petra; Voit, Brigitte (Polymer, 2015)
This study shows an additive assisted one-step melt mixing approach to produce composites of linear low density polyethylene (LLDPE) with carbon nanotubes (CNTs) which are nearly free of CNT agglomerates. Thereby, the influence of an nonionic additive namely polyoxyethylene cetyl ether as a dispersion additive during the CNT melt mixing process was investigated. It was analysed how the number of the polyoxyethylene repeating units or the exchange of the functional groups affect the dispersion mechanisms of multiwalled carbon nanotubes (MWCNT) namely Nanocyl™ NC7000 in LLDPE. Thereby the supposed CNT dispersion mechanism is explained as schematic overview. In summary, the CNT macrodispersion is improved if the number of polyoxyethylene repeating units increases. Through the addition of polyoxyethylene (20) cetyl ether the percolation threshold can be reduced to about 1 wt.% with a simultaneous homogeneous dispersion of CNTs. Additionally at an MWCNT loading of 2 wt.% and 8 wt.% of polyoxyethylene (20) cetyl ethers the strain at break increases by 113% in comparison to corresponding composite without the additive while modulus and stress at break generally decrease with additive addition.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Additives; Carbon nanotubes; Polymer-matrix composites (PMCs)